Pertimbangan Hukum Hakim Dalam Kasus Tindakan Pencurian Kendaraan Bermotor Yang Di Lakukan Oleh Anak - Alfons, Revalno; Titahelu, Juanrico Alfaromona Sumarezs; Taufik, Iqbal (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: one of the motor vehicle theft cases is the Ambon District Court decision No. No.12/PID.SUS-ANAK/2021/PN.AMB which states that Ammar Peisamal alias Ammar was convicted of "grave theft" as explained in the Criminal Code article 363 paragraph (1).Purposes of the Research: This study aims to examine and discuss the actions of the perpetrators who have fulfilled the elements in Article 363 paragraph (1) of the Criminal Code and examine and discuss the basis for the judge's legal considerations in imposing a prison sentence of 2 years and 6 months on the perpetrator.Methods of the Research: the research method used is normative legal research. The research approach is a statutory approach and a conceptual approach. The sources of legal materials used are primary, secondary and tertiary legal materials. The technique of gathering legal materials through literature studies and then analyzed through perspective using qualitative methods.Results of the Research: The results showed that the Ambon District Court Judge stated in his decision that the defendant had been legally and convincingly proven to have committed the crime of stealing this case and imposed a prison sentence on the defendant for 2 (two) years and 6 (six) months. The public prosecutor's indictment, the public prosecutor's demands and the judge's considerations in his decision have fulfilled all the elements of the offense and the conditions for imposing a sentence on the defendant. This is based on the examination at trial where the evidence submitted by the public prosecutor includes the statements of the witnesses and the statements of the accused which are interrelated. The testimony of the defendant admitted his actions and regretted it.